2015
DOI: 10.3892/ijo.2015.3247
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl trisulfide induces apoptosis by suppressing NF-κB signaling through destabilization of TRAF6 in primary effusion lymphoma

Abstract: Abstract. The allyl sulfides, including diallyl sulfide (DAS), diallyl disulfide (DAD), and diallyl trisulfide (DAT), contained in garlic and members of the Allium family, have a variety of pharmacological activities. Therefore, allyl sulfides have been evaluated as potential novel chemotherapeutic agents. Here, we found that DAT inhibited nuclear factor-κB (NF-κB) signaling and induced apoptosis in primary effusion lymphoma (PEL), a subtype of non-Hodgkin's B-cell lymphoma caused by Kaposi's sarcoma-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 42 publications
3
36
0
Order By: Relevance
“…The pharmacological activity of garlic and the phytochemicals therein are being studied for the past three decades, of which the organosulphur compounds, especially allicin is one among the most-studied compounds (Mikaili et al 2013). Apart from the antimicrobial activity, the selected sulphur compounds from garlic have found to induce apoptosis by suppressing NF-kB signaling through destabilization of TRAF6 in primary effusion lymphoma (Shigemi et al 2016); attenuates oxidation stress, inflammation and endothelial dysfunction in hypercholesterolemic rabbits (El-Sheakh et al 2016) and protects against ischemic stroke in a rat model (Zhang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological activity of garlic and the phytochemicals therein are being studied for the past three decades, of which the organosulphur compounds, especially allicin is one among the most-studied compounds (Mikaili et al 2013). Apart from the antimicrobial activity, the selected sulphur compounds from garlic have found to induce apoptosis by suppressing NF-kB signaling through destabilization of TRAF6 in primary effusion lymphoma (Shigemi et al 2016); attenuates oxidation stress, inflammation and endothelial dysfunction in hypercholesterolemic rabbits (El-Sheakh et al 2016) and protects against ischemic stroke in a rat model (Zhang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the amplification of the TRAF6 locus is a somatic and frequent event in several human cancer types . Research findings showed that TRAF6 is important in the activation of the protein kinase complex IKK, which directly activates NF‐κB and, in turn, inhibits apoptosis . Therefore, TRAF6 is thought to function as a tumor activator by influencing apoptosis in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…2,22 Research findings showed that TRAF6 is important in the activation of the protein kinase complex IKK, which directly activates NF-κB and, in turn, inhibits apoptosis. 23,24 Therefore, TRAF6 is thought to function as a tumor activator by influencing apoptosis in cancer cells. However, our previous study showed that TRAF6 does not simply affect NF-κB signaling and apoptosis in cancer cells under 5 Thus, the precise role of TRAF6 in cancer has not been extensively investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of the IKK complex by sulfide was only investigated in non‐neuronal tissues. Garlic‐derived DATS promoted apoptosis in primary effusion lymphoma cells by inhibiting IKK activity, preventing proteasome‐driven degradation of IκB‐α and consequently suppressing NF‐κB (Shigemi et al ., ). Similar effect of DADS was detected in carbon tetrachloride‐exposed rat hepatocytes (Lee et al ., ).…”
Section: Putative Mechanisms Of Sulfide‐trpa1 Channel Interactionsmentioning
confidence: 97%